Stomoxys calcitrans (Diptera: Muscidae): Value for Veterinary Medicine. Review - M. A. Levchenko; E. A. Silivanova (Российский паразитологический журнал, 2020)
The purpose of the research is analysis and compilation of literature data on involvement of the stable fly Stomoxys calcitrans in the spread of livestock animal pathogens. Materials and methods. We have analyzed literature data from foreign sources over the past 30 years, which are indexed in the PubMed, Crossref, Web of Science and Scopus databases, about S. calcitrans as a potential vector of livestock animal pathogens. Results and discussion. A literature review is presented on assessment of economic impact by the stable fly S. calcitrans on animal husbandry, as well as possible involvement of the S. calcitrans imago in the transmission of viruses, bacteria, protozoa and helminths which are animal pathogens.